Analysis of Athletes ' Views on Digital Games - Tel, Mikail (Lahore Medical & Dental Coll, 2021)
The aim of this research is to determine athletes ' views on digital games and to determine their relationship to certain variables. 1521 (927 male, 594 female) athletes who continue their activities in different branches constitute the sample of the research. The research is in the screening model and has a descriptive quality. As a data collection tool, an online questionnaire was applied in which participants' demographic information, frequency of game play, the duration of game play with either mobile phone and desktop computer, and their digital game play status were surveyed. The data was analyzed using the SPSS statistical package program and the significance level was accepted as p<0.05. As a result, 60.9% of the research group were male, 35.5% were between the ages of 21 and 30, 59.2% were students, and 61.5% were undergraduates or graduates. 36.9% of participants were observed to play sports between 1-5 years, 27.5% were observed to play sports between 6-10 years, and 62.9% of them still continued their sports activities as athletes. In the study, it was determined that athletes played games in moderate frequency and preferred to play games at higher rates, daily, using their mobile phones. Participants expressed that they liked to play games and wanted to play again when they were successful in those games. Athletes stated that games are addictive, games with violent elements negatively affect people, and while excessive gameplay negatively affects social life, games also help them to relieve their boredom. They believe that games which are played with friends and family, etc. improved social skills, and they noted that games can be used for educational purposes, and that playing games helps them learn something new, but is mostly effective in filling out free time. Athletes also noted that they did not believe that playing digital games improved their athletic abilities specific to their sport in any way. A statistically significant difference was found when athletes' views on gender and digital games were examined. It was determined that there were statistically significant differences according to age, profession, year of playing sports, level in sports branch, frequency of playing games, duration of playing games with mobile phones, duration of playing games with computers, and that there were no statistically significant difference according to educational status. As a result, it was determined that the athletes in the research group played digital games with medium frequency and liked to play games. We believe that it will be useful for athletes to use digital games, the internet and social media to develop their skills in their branch of sports.
Keywords: Digital game; sports and Digital Game; athletes and digital game